1994
DOI: 10.1182/blood.v83.6.1535.1535
|View full text |Cite
|
Sign up to set email alerts
|

Plasma P-selectin is increased in thrombotic consumptive platelet disorders

Abstract: P-selectin is a 140-kD protein found in the alpha-granules of platelets and the Weibel-Palade bodies of endothelial cells that on cell activation is expressed on the cell surface and also secreted into the plasma. The secreted form of P-selectin, like plasma P-selectin, differed from platelet membrane P-selectin in that its molecular mass was approximately 3 kD lower under reducing conditions. Both the secreted and plasma forms of P-selectin contained cytoplasmic sequence as determined by Western blot analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
78
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(90 citation statements)
references
References 22 publications
11
78
0
1
Order By: Relevance
“…Interleukin-8 is a potent angiogenic factor [22]. Elevated levels of selectin-sP and IL-8 can be detected in the plasma of patients with atherosclerosis, hypertension and trombotic disorders, but we need to fully investigate whether these markers may be risk factors for atherosclerosis [23,24]. Our data show a significantly increased level of selectin-sP in patients with unstable coronary heart disease in comparison with patients with stable coronary heart disease, and a nonsignificantly increased level in comparison with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-8 is a potent angiogenic factor [22]. Elevated levels of selectin-sP and IL-8 can be detected in the plasma of patients with atherosclerosis, hypertension and trombotic disorders, but we need to fully investigate whether these markers may be risk factors for atherosclerosis [23,24]. Our data show a significantly increased level of selectin-sP in patients with unstable coronary heart disease in comparison with patients with stable coronary heart disease, and a nonsignificantly increased level in comparison with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…What is the pathophysiological relevance of cP-selectin? Higher than normal plasma levels of cP-selectin have been found in various diseases, including peripheral vascular disease (Blann et al, 1995), unstable angina pectoris (Ikeda et al, 1995), myocardial infarction Wu et al, 1993), or thrombotic diseases (Katayama et al, 1993;Chong et al, 1994). These disease states are associated with damage of EC and thrombus formation, processes which could be mediated by P-selectin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, impaired fibrinolysis and reduced production of prostacyclin have been implicated in the development of TTP [15]. Several authors have demonstrated that TTP plasma, as opposed to ITP plasma, causes activation and induces injury to endothelial cells [47,48], manifested by a significant increase in endothelial microparticles [47][48][49], e-selectin, p-selectin [50], thrombomodulin [51], and b-thromboglobulin [52], and all markers of endothelial cell and platelet activation, and induces increased expression of adhesion molecules such as ICAM-1 and VCAM-1 [48]. In addition, anti-endothelial cell antibodies (AECA) have been demonstrated in patients with TTP [53].…”
Section: Endothelial Activation and Hypercoagulabilitymentioning
confidence: 99%